The Influence of Self-regulated Learning, Adversity Quotient, Self-Efficacy, and Learning Motivation on Academic Achievement - Ridha, Ahmad Rifky; Sanusi, Wahidah; Mulbar, Usman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
This ex-post facto quantitative study seeks to analyze the influence of Self-Regulated Learning, Adversity Quotient, Self-Efficacy, and Learning Motivation on the Academic Achievement of 8th Grade Students at MTs Madani Alauddin, utilizing the complete population of 8th Grade students at the institution. This research employed cluster random sampling, yielding a sample size of 105 people. The questionnaire was employed to gather data on Self-Regulated Learning, Adversity Quotient, Self-Efficacy, and Learning Motivation among eighth-grade students at MTs Madani Alauddin. The research data were examined employing descriptive and inferential statistics through Partial Least Squares Structural Equation Modeling (SEM-PLS). The research findings indicate that self-regulated learning exerts both direct and indirect influences on academic accomplishment, with the direct influence being more significant than the indirect influence. The adversity quotient exerts both direct and indirect effects on academic achievement, with the direct effect being more pronounced than the indirect effect. Self-efficacy exerts both direct and indirect effects on academic accomplishment, with the direct effect being more pronounced than the indirect effect. The urge to learn directly influences academic performance.